Legal Analysis of the Transfer of Land Rights of PTPN I in the Development of the Citrland Project - Adnan, Muhammad Ali; Arkan, Muhammad; Siburian, Lamroni; Sunarto, Atika (Al-Risalah, 2026)
The transfer of land rights with the status of Right of Cultivation (HGU) owned by PT Perkebunan Nusantara I in the development of the Citraland project emphasizes aspects of legal certainty, administrative mechanisms, and the legal responsibilities of the parties involved. This research employs a normative juridical method with statutory and conceptual approaches, through an examination of agrarian legal norms, regulations governing the management of State-Owned Enterprise assets, legal doctrines, and relevant legal practices. The results of the study indicate that the transfer of HGU cannot be carried out directly to the developer; instead, it must first involve the relinquishment of the right so that the land reverts to state land, followed by the granting of new land rights by the land authority in accordance with spatial planning designations and construction permits. Legal responsibility is reciprocal in nature, whereby PTPN I is obligated to ensure the legality and accountability of state asset management, while the developer is required to fulfill all requirements for the acquisition of land rights and development permits in order to provide legal certainty and protection for good-faith members of the public. This study affirms that compliance with the principles of legality, transparency, and accountability constitutes a fundamental prerequisite to prevent disputes and potential state losses in the transfer of strategic assets.